Rehabilitation Needs of Head and Neck Cancer Patients and Stakeholders: Case Study - Karampela, Maria; Porat, Talya; Mylonopoulou, Vasiliki; Isomursu, Minna (Frontiers in Oncology, 2021)
Background: The incidents of Head and Neck cancer (HNC) are rising worldwide, suggesting that this type of cancer is becoming more common. The foreseen growth of incidents signifies that future rehabilitation services will have to meet the needs of a wider population. Objective: The aim of this paper is to explore the needs of patients, caregivers and healthcare professionals during HNC rehabilitation. Methods: This paper reports the empirical findings from a case study that was conducted in a cancer rehabilitation center in Copenhagen to elicit the needs of HNC cancer patients, informal caregivers and healthcare professionals. Results: Four areas of needs during the rehabilitation process were identified: service delivery, emotional, social and physical needs. Service delivery needs and emotional needs have been identified as the most prevalent. Conclusions: Stakeholders’ needs during the rehabilitation process were found to be interrelated. All stakeholders faced service delivery challenges in the form of provision and distribution of information, including responsibilities allocation between municipalities, hospitals and rehabilitation services. Emotional and social needs have been reported by HNC patients and informal caregivers, underlining the importance of inclusion of all actors in the design of future healthcare interventions. Connected Health (CH) solutions could be valuable in provision and distribution of information.